Evaluating the effectiveness of audit committees in Singapore - Kuek, Alvin Chye Seng (2014)
The purpose of this research undertaking is to evaluate the effectiveness of audit committees in Singapore. Proponents of the audit committee concept assert that the active development of the audit committee concept would bolster public confidence in the financial statements. However, this would only be true if the audit committees are effective in discharging their duties. Therein lies the importance of our research undertaking; by assessing the effectiveness of audit committees, we would be able to gauge whether the audit committees do in fact enhance the financial reporting process. In addition, based on the study, certain recommendations are made, hopefully, for improving the functioning of audit committees, thereby enhancing their effectiveness.